К вопросу о динамике численности городских населенных пунктов Пермского края (Географический вестник=Geographical bulletin, 2017)
Рассмотрена динамика численности населения городских населенных пунктов Пермского края в 1989 – 2009 гг. в разрезе группировок по размеру и зональных систем расселения. Дается предварительная оценка взаимосвязи выявленных тенденций с проблемами качества среды и процессами трансформации функциональной структуры городов и поселков городского типа региона.ON THE DYNAMICS OF URBAN SETTLEMENTS OF PERM REGION The processes of depopulation of the urban population of Perm region in the last twenty years is a persistent problem, reaching settlements of all sizes and all the zonal system of settling the region. Observed a definite relationship between the magnitude of the fall population of cities and towns, and the depth of the problems of environmental quality and the transformation of the functional structure. However, the decrease in population is typical for a number of cities and towns are relatively high quality environment and have a functional structure of activities with the favorable economic environment. Requires a comprehensive analysis of the dynamics of the population depending on various factors, taking into account the territorial specificities, based on detailed statistical information.K e y w o r d s: population dynamics; transformation of the functional structure.